Adverse childhood experiences and dental anxiety among Chinese adults in Hong Kong: a cross-sectional study - Wong, Natalie Sui Miu; Yeung, Andy Wai Kan; McGrath, Colman Patrick; Leung, Yiu Yan (Frontiers in Psychology, 2024)
Introduction This study aimed to investigate the relationship between adverse childhood experiences (ACEs) and dental anxiety among Chinese adults in Hong Kong. Methods A cross-sectional survey was conducted at a university in Hong Kong. The recruiting period and data collection started in January 2023 and ended in June 2023. Participants completed an online questionnaire that assessed ACEs (using the Adverse Childhood Experiences International Questionnaire – ACE-IQ) and dental anxiety (using the Modified Dental Anxiety Scale – MDAS and Dental Fear Survey – DFS). The study examined the impacts of both cumulative (i.e., total number) and independent ACE components on dental anxiety. To explore the relationships between cumulative ACEs, individual ACE components and dental anxiety (MDAS and DFS score), Pearson correlations, linear regression and logistic regression were conducted. Results Significant associations were observed between ACEs and dental anxiety among 171 subjects. Cumulative ACEs were positively correlated with MDAS scores (r = 0.169, p = 0.027) and DFS scores (r = 0.253, p < 0.001). The odds of an individual having high dental anxiety increased by 26–43% for every additional increase in the number of ACEs. Individual types of ACEs, such as emotional and physical neglect, sexual abuse, and household substance abuse, significantly influenced the likelihood of having high dental anxiety. Discussion The results showed a positive association between ACEs and dental anxiety, highlighting the impact of ACEs on dental anxiety. Dental practitioners should consider inquiring about a patient’s ACE history to develop personalized treatment plans.